PENGGUNAAN MEDIA ANIMASI DAN MODEL STAD DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - Anggun Srirahayu; Budiyono Budiyono; Yarmaidi Yarmaidi (JPG (Jurnal Penelitian Geografi), 2015)
The research was purpose to examine: the using of animation media and STAD learning model (students teams achievement division) in effort to increase the activities and learning results of Geography in class X1 at SMA Al-Azhar 3 Bandar Lampung 2015. This research used classroom action research as the method. By using 3 cycles of learning. The data collecting technique was done by observation, interview, test, documentation, and assisted partner teacher. This results indicated that: (1) In the first cycle there were 33.33% active students in learning with 23.33% of the learning results achieve a minimum completeness criteria ?70. In the second cycle increased by 45.45% at learning activities with learning results increased to 33.33%. The third cycle increased to 70.96% at learning activities with learning results became 74.19% from all student. (2) It turned out that using the animation media and STAD model can increase students activities and learning results of Geography.Penelitian ini bertujuan mengkaji: Penggunaan Media Animasi dan Model Pembelajaran STAD dalam upaya meningkatkan aktivitas dan hasil belajar geografi siswa kelas X1 SMA Al-Azhar 3 Bandar Lampung tahun 2015. Penelitian ini menggunakan metode penelitian tindakan kelas, dengan 3 siklus pembelajaran. Pengumpulan data dengan teknik observasi, wawancara, tes, dokumentasi, dan dibantu guru mitra. Hasil penelitian menunjukkan: (1) Pada siklus I terdapat sebanyak 33,33% siswa aktif dalam memperhatikan pembelajaran dengan hasil belajar 23,33% mencapai kriteria ketuntasan minimal ? 70. Pada siklus II aktivitas belajar meningkat sebanyak 45,45% dengan hasil belajar meningkat menjadi 33,33%. Pada siklus III aktivitas belajar meningkat menjadi 70,96% dengan hasil belajar menjadi 74,19% dari seluruh siswa. (2) Ternyata penggunaan media animasi dan model STAD dapat meningkatkan aktivitas dan hasil belajar geografi siswa.Kata kunci: aktivitas belajar, hasil belajar, media animasi dan model STAD